PERAN DAN KEWENANGAN NOTARIS SEBAGAI PROFESI PENUNJANG PASAR MODAL DI INDONESIA - Putra Handayana, I Gusti Agung; Puspawati, I Gusti Ayu (Kertha Semaya : Journal Ilmu Hukum, 2014)
The Capital Market is one part of money market (financial Market) in general besides money market which has important role for the national development, particularly for the development of business as one of the alternative source external financing by a company. This paper uses analytical methods and approaches normative statutory. The purpose of this paper is to reveal the extent of the role and authority of the notary in The Capital Market. In conclusion that its function as a notary in the state officials in The Capital Market besides subject and obedient to the laws governing The Capital Market legislation.
Keywords: Notary, Financial Market